Cost of inaction: a framework to estimate the economic cost of missing a patient with tuberculosis in the Indian context - Brooks, Meredith B; Pingali, Viswanath; Nicholson, Tom; Keshavjee, Salmaan (BMJ open, 2023)
ObjectivesTo estimate the economic impact of failure to find and treat tuberculosis disease and prevent tuberculosis infection from progressing to active disease.DesignEstimating the economic cost of not finding and treating a patient suffering from tuberculosis.SettingEstimation methodology is developed in the Indian context, as informed by local costs and reported tuberculosis epidemiology.ParticipantsNo individual participants were included.Primary and secondary outcome measuresThe primary outcome measure is the total cost of patients with drug-susceptible and drug-resistant tuberculosis who are and are not found and treated by tuberculosis programmes, including costs for medications, lost productivity, healthcare services and furthered transmission. We calculate the economic burdens by varying the number of individuals a person sick with tuberculosis infects (10 or 15 people) and the risk of progression to tuberculosis disease if infected (5 or 8%). The secondary outcome measure is the amount saved by finding a patient early or who would not have otherwise been found. All costs are presented in US dollars (exchange rate: 72 Indian rupees/1 US$).ResultsBy finding and treating a patient early before furthered transmission occurs—or stopping progression of tuberculosis infection to tuberculosis disease with preventive therapy—the Indian health system can save US$5502 to US$15 825 and US$5846 to US$25 575, for each individual with drug-susceptible and drug-resistant tuberculosis, respectively, across scenarios.ConclusionsThese estimates provide crude, lower bounds for the potential costs of not appropriately diagnosing and treating a single patient with active tuberculosis in a timely manner, or preventing a patient with tuberculosis infection from progressing to active disease. The actual financial burden on society is far higher than estimated using this simple, short-term cost-effective analyses. Our results highlight the limitations of tuberculosis costing models to date, and demonstrate the importance of accounting for airborne transmission of tuberculosis.